Assessing adoption factors for additive manufacturing: Insights from case studies - Robert B. Handfield; James Aitken; Neil Turner; Tillmann Boehme; Cecil Bozarth (Logistics, 2022)
Background: Research on Additive Manufacturing [AM] provides few guidelines for successful adoption of the technology in different market environments. This paper seeks to address this gap by developing a framework that suggests market attributes for which the technology will successfully meet a need. We rely on classical technology adoption theory to evaluate the challenges and opportunities proffered by AM. Methods: We apply a framework of technology adoption and assess these parameters using seven case studies of businesses that have successfully adopted AM technology. Results: We find that successful business adoption is highly associated with the relative advantage of AM to rapidly deliver customized products targeted to niche market opportunities. Conclusions: Our findings provide a decision framework for AM equipment manufacturers to employ when evaluating AM technology across various market environments. All five adoption characteristics were found to be important however, the primary decision criterion is based on the relative advantage of AM over other, traditional, technologies. From a practitioner perspective, our research highlights the importance of AM in attaining a competitive advantage through responsive, customized production which can address the needs of niche markets.
Keywords: 650; additive manufacturing; adoption of innovation; case study research